1995
DOI: 10.1007/bf00705642
|View full text |Cite
|
Sign up to set email alerts
|

The role ofSaccharomyces cerevisiae Cdc40p in DNA replication and mitotic spindle formation and/or maintenance

Abstract: Successful progression through the cell cycle requires the coupling of mitotic spindle formation to DNA replication. In this report we present evidence suggesting that, in Saccharomyces cerevisiae, the CDC40 gene product is required to regulate both DNA replication and mitotic spindle formation. The deduced amino acid sequence of CDC40 (455 amino acids) contains four copies of a beta-transducin-like repeat. Cdc40p is essential only at elevated temperatures, as a complete deletion or a truncated protein (deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 69 publications
0
27
1
Order By: Relevance
“…Splicing defects in prp17 mutant alleles+ A: RT-PCR analysis for splicing of ACT1 transcripts+ cDNA was generated using a primer 59 of the ACT1 branch point; and PCR was done with the same primer together with a primer at the 59 end of Exon 1 and another primer in the intron downstream to the 59 splice site+ Total RNA (15 mg) used was from each of the six different strains denoted above the lanes (Wild type, prp17⌬::LEU2, prp17⌬::LEU2ϩpG1mut2(AAAI), prp17⌬::LEU2ϩpG1mut2(EGGL), prp17⌬::LEU2ϩpG1⌬142-161, and prp17⌬::LEU2ϩmut4 ) and was prepared from cells grown at both permissive and nonpermissive temperatures, as indicated at bottom+ The PCR products from the pre-mRNA and Lariat intermediate are indicated+ End-labeled pBR322 digested with HinfI was used as molecular weight marker+ B: RT-PCR analysis of PRP24 transcripts, from a nonintron-containing gene, as control+ Total RNAs prepared from the strains denoted in A were used for RT-PCR with primers specific to a segment of PRP24 mRNA+ Blanco, 1998)+ In fact, we observed uniform nuclear staining of HAyPrp17 (Fig+ 6)+ In addition, all mutant proteins showed exclusive nuclear localization except for ⌬42-61 and the N-terminal deletions ⌬2-100 through ⌬2-140 (Fig+ 6 and data not shown)+ Thus, whenever amino acids 42-61 were absent, the protein accumulated in the cytoplasm+ This basic stretch of amino acids (NNIHKRKSHFTKSELKRRRK) was previously predicted to be the nuclear localization signal (NLS) for this protein (Vaisman et al+, 1995)+ Our data adds functional support that this is indeed the NLS+ Significantly, the ⌬42-61 protein, as well as ⌬2-100 and ⌬2-110, were still able to rescue the temperature-sensitive phenotype when overexpressed in the knockout strain+ This suggests that a minor, but functionally sufficient, level of yPrp17p accumulates in the nucleus in this strain+ Genetic interactions among prp17 and U5 snRNA mutations U5 snRNA is essential in yeast and is required for mammalian in vitro splicing+ Genetic and crosslinking studies have implicated the invariant loop I sequence of U5 snRNA in an interaction with exon sequences adjacent to the splice sites O'Keefe et al+, 1996;Seshadri et al+, 1996;Xu et al+, 1998)+ Detailed analyses of loop I sequences revealed that their interaction with exonic sequences are not necessary for the first catalytic step but are critical for the second step of splicing in yeast (O'Keefe & Newman, 1998)+ In addition, a number of U5-associated protein factors are required at this step+ One likely function for these factors is in maintaining an active conformation of the catalytic spliceosome+ Consistent with these findings, are reports that alleles of PRP17 interact genetically with loop I of U5 snRNA+ prp17-3/slu4-1 was isolated as a temperature-sensitive mutation that was synthetically lethal with a specific U98A mutation in loop I of U5 snRNA + Later it was shown that the prp17-3 allele was allele specific in its interaction with U5 snRNA and that three other alleles, prp17-1, prp17-2, and prp17Gb3-9, did not show this interaction (Seshadri et al+, 1996; Table 1, bottom)+ The mutation in prp17-3 lies in the N-terminal domain that is not conserved between the yeast and the human proteins+ More recently, another temperature-sensitive allele of PRP17, prp17-100/slt15, was identified in a screen for synthetic lethality with U2 snRNA mutations (Xu et al+, 1998)+ The mutation in this allele has not been mapped, but it was lethal in combination with both the U98A and the UU97,99CC U5 snRNA mutations (Xu et al+, 1998; …”
Section: Subcellular Localization Of Yprp17p and The Mutated Proteinsmentioning
confidence: 88%
“…Splicing defects in prp17 mutant alleles+ A: RT-PCR analysis for splicing of ACT1 transcripts+ cDNA was generated using a primer 59 of the ACT1 branch point; and PCR was done with the same primer together with a primer at the 59 end of Exon 1 and another primer in the intron downstream to the 59 splice site+ Total RNA (15 mg) used was from each of the six different strains denoted above the lanes (Wild type, prp17⌬::LEU2, prp17⌬::LEU2ϩpG1mut2(AAAI), prp17⌬::LEU2ϩpG1mut2(EGGL), prp17⌬::LEU2ϩpG1⌬142-161, and prp17⌬::LEU2ϩmut4 ) and was prepared from cells grown at both permissive and nonpermissive temperatures, as indicated at bottom+ The PCR products from the pre-mRNA and Lariat intermediate are indicated+ End-labeled pBR322 digested with HinfI was used as molecular weight marker+ B: RT-PCR analysis of PRP24 transcripts, from a nonintron-containing gene, as control+ Total RNAs prepared from the strains denoted in A were used for RT-PCR with primers specific to a segment of PRP24 mRNA+ Blanco, 1998)+ In fact, we observed uniform nuclear staining of HAyPrp17 (Fig+ 6)+ In addition, all mutant proteins showed exclusive nuclear localization except for ⌬42-61 and the N-terminal deletions ⌬2-100 through ⌬2-140 (Fig+ 6 and data not shown)+ Thus, whenever amino acids 42-61 were absent, the protein accumulated in the cytoplasm+ This basic stretch of amino acids (NNIHKRKSHFTKSELKRRRK) was previously predicted to be the nuclear localization signal (NLS) for this protein (Vaisman et al+, 1995)+ Our data adds functional support that this is indeed the NLS+ Significantly, the ⌬42-61 protein, as well as ⌬2-100 and ⌬2-110, were still able to rescue the temperature-sensitive phenotype when overexpressed in the knockout strain+ This suggests that a minor, but functionally sufficient, level of yPrp17p accumulates in the nucleus in this strain+ Genetic interactions among prp17 and U5 snRNA mutations U5 snRNA is essential in yeast and is required for mammalian in vitro splicing+ Genetic and crosslinking studies have implicated the invariant loop I sequence of U5 snRNA in an interaction with exon sequences adjacent to the splice sites O'Keefe et al+, 1996;Seshadri et al+, 1996;Xu et al+, 1998)+ Detailed analyses of loop I sequences revealed that their interaction with exonic sequences are not necessary for the first catalytic step but are critical for the second step of splicing in yeast (O'Keefe & Newman, 1998)+ In addition, a number of U5-associated protein factors are required at this step+ One likely function for these factors is in maintaining an active conformation of the catalytic spliceosome+ Consistent with these findings, are reports that alleles of PRP17 interact genetically with loop I of U5 snRNA+ prp17-3/slu4-1 was isolated as a temperature-sensitive mutation that was synthetically lethal with a specific U98A mutation in loop I of U5 snRNA + Later it was shown that the prp17-3 allele was allele specific in its interaction with U5 snRNA and that three other alleles, prp17-1, prp17-2, and prp17Gb3-9, did not show this interaction (Seshadri et al+, 1996; Table 1, bottom)+ The mutation in prp17-3 lies in the N-terminal domain that is not conserved between the yeast and the human proteins+ More recently, another temperature-sensitive allele of PRP17, prp17-100/slt15, was identified in a screen for synthetic lethality with U2 snRNA mutations (Xu et al+, 1998)+ The mutation in this allele has not been mapped, but it was lethal in combination with both the U98A and the UU97,99CC U5 snRNA mutations (Xu et al+, 1998; …”
Section: Subcellular Localization Of Yprp17p and The Mutated Proteinsmentioning
confidence: 88%
“…Step II splicing factors are responsible for the selection of correct 39 splice sites, and some had been characterized in other systems to be nonessential and play a role in the efficient progression through cell cycle transitions (e.g., Cdc40p; Vaisman et al, 1995;Boger-Nadjar et al, 1998). In fact in yeast, many splicing factors were defined by mutations that had been uncovered in cell cycle mutant screens (e.g., Prp3p, Prp8p, Prp22p, and Cef1p; Shea et al, 1994;Hwang and Murray, 1997;McDonald et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Each family member has between four and 10 copies of the WD40 repeats. In general, WD40 repeat proteins have been associated with a diverse range of cellular processes, including RNA processing, transcriptional regulation (Williams et al 1991;Hoey et al 1993), mitotic spindle formation (de Hostos et al 1991;Vaisman et al 1995), regulation of vesicle formation and vesicular trafficking (Pryer et al 1993), and control of cell division (Feldman et al 1997).…”
Section: Wd40 Repeat Proteins Are Important For a Variety Of Cellularmentioning
confidence: 99%